Incorporation of shear thickening fluid effects into computational modelling of woven fabrics subjected to impact loading: A review. Issue 3 (September 2020) - Weerasinghe, Dakshitha; Mohotti, Damith; Anderson, Jeremy
Soft armour consisting of multi-layered high-performance fabrics are a popular choice for personal protection. Extensive work done in the last few decades suggests that shear thickening fluids improve the impact resistance of woven fabrics. Shear thickening fluid–impregnated fabrics have been proven as an ideal candidate for producing comfortable, high-performance soft body armour. However, the mechanism of defeating a projectile using a shear thickening fluid–impregnated multi-layered fabric is not fully understood and can be considered as a gap in the research done on the improvement of soft armour. Even though considerable progress has been achieved on dry fabrics, limited studies have been performed on shear thickening fluid–impregnated fabrics. The knowledge of simulation of multi-layered fabric armour is not well developed. The complexity in creating the geometry of the yarns, incorporating friction between yarns and initial pre-tension between yarns due to weaving patterns make the numerical modelling a complex process. In addition, the existing knowledge in this area is widely dispersed in the published literature and requires synthesis to enhance the development of shear thickening fluid–impregnated fabrics. Therefore, this article aims to provide a comprehensive review of the current methods of modelling shear thickening fluid–impregnated fabrics with a critical analysis of the techniques used. The review is preceded by an overview of shear thickening behaviour and related mechanisms, followed by a discussion of innovative approaches in numerical modelling of fabrics. A novel state-of-the-art means of modelling shear thickening fluid–impregnated fabrics is proposed in conclusion of the review of current methods. A short case study is also presented using the proposed approach of modelling.